2011
DOI: 10.1016/j.toxicon.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of membrane-disruptive lytic compounds from the marine dinoflagellate Alexandrium tamarense

Abstract: a b s t r a c tCertain allelochemicals of the marine dinoflagellate Alexandrium tamarense cause lysis of a broad spectrum of target protist cells but the lytic mechanism is poorly defined. We first hypothesized that membrane sterols serve as molecular targets of these lytic compounds, and that differences in sterol composition among donor and target cells may cause insensitivity of Alexandrium and sensitivity of targets to lytic compounds. We investigated Ca 2þ influx after application of lytic fractions to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…The same might be the reason for a reduced lytic activity upon N starvation; however, nothing is yet known of the elemental composition of Alexandrium allelochemicals. What we know is that at least one group of lytic allelochemicals produced by A. tamarense comprises a suite of large non-proteinaceous and probably nonpolysaccharide compounds between 7 and 15 kDa (Ma et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The same might be the reason for a reduced lytic activity upon N starvation; however, nothing is yet known of the elemental composition of Alexandrium allelochemicals. What we know is that at least one group of lytic allelochemicals produced by A. tamarense comprises a suite of large non-proteinaceous and probably nonpolysaccharide compounds between 7 and 15 kDa (Ma et al 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported that dissolved STX, A. tamarense cell content, and cellfree medium did not affect the hatching of scallops, but resuspended algal cell and cell fragments did, also showing that the negative effects on egg hatching are associated with uncharacterized cytotoxic compounds located on the cell surface of A. tamarense, rather than exuded compounds. In more recent reports, the lytic activity of Alexandrium against protists seemed to act on external cell membranes (Ma et al, 2009), as was the case of lytic compounds from A. tamarense that increased membrane permeability to Ca 2+ ions without specifically binding to calcium ion channels (Ma et al, 2011), and lytic compounds from three strains of A. tamarense complex whose toxicity were related to reactive oxygen species (ROS) and/or to secondary compounds produced by ROS-induced lipid peroxidation (Flores et al, 2012); however, cytotoxicheatlabile exotoxin (Lush et al, 2001), hemolytic proteinaceous exotoxin (Emura et al, 2004), and a polysaccharide-based cytotoxic compound (Yamasaki et al, 2008) were recently isolated from Alexandrium minutum, A. taylori, and A. tamarense, respectively, showing that both exudates and cell contact are possible mechanisms for the observed deleterious effects of Alexandrium spp. that could be strain-specific, and both mechanisms could have been implicated in the observed effects of A. affine and A. catenella on embryos and trochophores in the present study.…”
Section: Role Of Paralytic Shellfish Toxins Brevetoxins and Other Tmentioning
confidence: 99%
“…In order to further illuminate the factors influencing synthesis and accumulation of the lytic compounds of Alexandrium spp., highly targeted datasets combining a high number of measurements of allelochemical activity with finely graded variations of the physiological parameters seem most promising. The elucidation of the chemical composition and structure of those compounds is currently under way (Ma et al, 2009(Ma et al, , 2011. …”
Section: Factors Influencing Toxin Content and Allelochemical Activitymentioning
confidence: 99%